Hobbes and the economic, social and cultural rights of the universal declaration of human rights - Hernández, Javier; Dussan, Santiago (The Age of Human Rights Journal, 2021)
This article argues that the conceptions of natural rights in Hobbes’s theory and of economic, social and cultural rights in the Universal Declaration of Human Rights have three common features that serve to justify the thesis that a satisfactory order of coexistence cannot be achieved without extensive state power. Both conceptions identify rights with interests whose satisfaction is considered paramount. Both perspectives see the state as the shaper of the legal order that rights do not create. Finally, both see the state as the entity that must monopolize the management of individual interests represented in rights. This article suggests that these findings are paradoxical when confronted with the main motivation behind the drafting of the Declaration.